Объяснение:
Zn(NO3)2 + 2NaOH = Zn(OH)2 ↓+ 2NaNO3
Zn(2+) + 2NO3(-) + 2Na(+) + 2OH(-) = Zn(OH)2↓ + 2Na(+) + 2NO3(-)
Zn(2+) + 2OH(-) = Zn(OH)2↓
3Zn(NO3)2 + 2H3PO4 = Zn3(PO4)2↓ + 6HNO3
3Zn(2+) + 6NO3(-) + 6H(+) + 2PO4(3-) = Zn3(PO4)2↓ + 6H(+) + 6NO3(-)
3Zn(2+) + 2PO4(3-) = Zn3(PO4)2↓
3Zn(NO3)2 + 2Al = 2Al(NO3)3 +3 Zn
Zn(NO3)2 + K2S = ZnS↓ + 2KNO3
Zn(2+) + 2NO3(-) + 2K(+) + S(2-) = ZnS↓ + 2K(+) + 2NO3(-)
Zn(2+) + S(2-) = ZnS↓
Zn(NO3)2 + H2O = ZnOHNO3 + HNO3
Zn(2+) + 2NO3(-) + H2O = ZnOH(+) + NO3(-) + H(+) + NO3(-)
Zn(2+) + H2O = ZnOH(+) + H(+)